2018
DOI: 10.3390/ijerph15040589
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of 2,4-Dichlorophenol and 2,5-Dichlorophenol in Urine of Korean Adults

Abstract: Humans are exposed to the environmental pollutants 2,4-dichlorophenol (2,4-DCP) and 2,5-dichlorophenol (2,5-DCP) through air, the use of water and the consumption of products. In this study, we evaluated the urinary concentrations of these compounds in Korean people between the ages of 18 to 69 years, by making use of data from the Korean National Human Biomonitoring Survey that was completed in 2009. Of 1865 representative Koreans, 63.4% and 97.9% were found to have concentrations of 2,4-DCP and 2,5-DCP > 0.0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…9094 In NHANES 2005–2008, 2,5-dichlorophenol concentrations were positively associated with BMI, 20 but BMI was not associated with 2,5-dichlorophenol concentrations in SELF, the Healthy Start study, or the KNHBS. 79, 87 Our findings on BMI and triclosan also differed from those of other studies: we found no association between BMI and triclosan concentrations, but, in NHANES 2003–2010, the Healthy Start study, and the MIREC study, triclosan concentrations were inversely associated with BMI. 23, 74, 79 In NHANES 2013–2014, having a higher body surface area was associated with higher levels of triclocarban.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…9094 In NHANES 2005–2008, 2,5-dichlorophenol concentrations were positively associated with BMI, 20 but BMI was not associated with 2,5-dichlorophenol concentrations in SELF, the Healthy Start study, or the KNHBS. 79, 87 Our findings on BMI and triclosan also differed from those of other studies: we found no association between BMI and triclosan concentrations, but, in NHANES 2003–2010, the Healthy Start study, and the MIREC study, triclosan concentrations were inversely associated with BMI. 23, 74, 79 In NHANES 2013–2014, having a higher body surface area was associated with higher levels of triclocarban.…”
Section: Discussioncontrasting
confidence: 95%
“…19 Inconsistency across analyses of NHANES data may relate to differences in how income variables were modeled. In SELF, the NCS Vanguard Study, 82 and the Korean National Human Biomonitoring Survey (KNHBS), 87 a cross-sectional study of 1 865 women and men aged 18–69 years recruited in 2009, no relation was observed between 2,4-dichlorophenol or 2,5-dichlorophenol concentrations and income, while higher concentrations of 2,5-dichlorophenol were observed among low-income Healthy Start study participants. 79 One analysis of NHANES 2001–2008 data observed higher concentrations of 2,4-dichlorophenol and 2,5-dichlorophenol among both low income and high income non-Hispanic Blacks compared with high income non-Hispanic Whites, 88 while an analysis of NHANES 2005–2008 observed an inverse association with education and income for both compounds.…”
Section: Discussionmentioning
confidence: 99%
“…2,4-DCP is the most common organochlorine compound and is a key component in products of herbicides 2,4-dichlorophenoxyacetate (2,4-D) and antiseptics, pharmaceutical intermediates (Park & Kim, 2018). It is by-products of the treatment of drinking and wastewaters with chlorination.…”
Section: Introductionmentioning
confidence: 99%
“…Deierlein showed that phthalates—specifically low-molecular weight phthalates (monoethyl phthalate [MEP], a metabolite of diethyl phthalate (DEP); mono-n-butyl phthalate [MBP], a metabolite of di-n-butyl phthalate (DBP), and mono-isobutyl phthalate [MiBP], a metabolite of di-isobutyl phthalate (DiBP))—had slight associations with girls’ anthropometric outcomes [ 11 ]. These substances are readily present in our daily lives, since consumer products usually use parabens as preservatives, building and food packaging materials use phthalates as plasticizers, and the production of pharmaceutical and agricultural products uses 2,5-DCP as a chemical intermediate [ 12 14 ]. We can easily contact these environmental endocrine-disrupting chemicals via gastrointestinal intake, dermal contact, and applying products that contain these chemicals [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%